EVALUASI SIMPANG 3 (TIGA) TAK BERSINYAL JL.D.I.PANJAITAN – JL.PANGERAN MUHAMMAD NOOR – JL.MAYJEND PANJAITAN DI KOTA SAMARINDA - S, SONY (KURVA S JURNAL MAHASISWA, 2014)
Transportation in the city of Samarinda is an important factor that will affect the development of the region , which will support the potential of natural resources , human resources , and other economic potential . Samarinda City has a high level of congestion , congestion is caused by the increase in population triggered the ownership of the vehicle is not balanced by the roads .. Traffic problems often encountered in the cities that are growing , such as the city of Samarinda , the problem of traffic congestion and kesemberautan often occur at a crossroads , especially not signalized intersection , the intersection of 3 ( three ) JL.DIPanjaitan - JL.Pangeran Muhammad Noor - JL.Mayjend Panjaitan In Samarinda .. it is influenced by several factors , including the increasing volume of traffic and road infrastructure supporting factors . The results of the analysis obtained by using the form usig - I and - II usig Guidelines Indonesian Highway Capacity Manual ( MKJI ) 1997 capacity ( C ) initial conditions (existing ) intersection of  2667 smp / hour and the traffic flow ( Q ) of  4487 smp / h by entering the formula : DS = Q / C and the ratio of the total intersection of 0.5 included the importance of the DS of 1.70 > 0.85 ( DS which hinted ) . From the calculation results in a very high degree of saturation intersection experiencing conflicts and interlocking . From the calculation of initial conditions (existing ) then do some improvement alternatives